MODEL ALTMAN SCORE DAN GROVER SCORE : MENDETEKSI FINANCIAL DISTRESS PADA PERUSAHAAN RITEL DI INDONESIA - Patmawati Patmawati; Muhammad Hidayat; Muhammad Farhan (AKUNTABILITAS, 2020)
This study aims to detect financial distress of listed retail companies at Indonesian Exchange using Altman Score and Grover Score Model. The samples are go public companies in Indonesia, which consist of 20 retail companies. Structural Equation Model (SEM) was employed as the analysis method using PLS software. The result shows that Altman Score Model has positive impact toward financial distress. High score on Altman Score indicates poor performance of a company. Further, Grover Score model has positive impact toward financial distress on retail companies which are go public circa 2015-2018. Higher score of grover score indicates a company has been suffering financial distress. Lastly, we inference that Altman Score Model is more accurate in detecting financial distress compared to Grover Score Model